UTILIZATION OF LIVESTOCK WASTE AS COMPOST FERTILIZER IN PARDOMUAN MOTUNG VILLAGE, AJIBATA DISTRICT, TOBA SAMOSIR REGENCY - Sadeli, Achmad; Ginting, Adil; Tarigan, Lina (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The use of compost can improve soil physical and microbiological properties. Compost contains nutrients such as nitrogen and phosphate in the form of complex compounds of argon, protein, and humic that are difficult for plants to absorb. Various efforts to improve nutrient status in compost have been carried out, such as the addition of natural ingredients of bone meal, dried blood flour, banana bark skin and biofertilizer. a lot of waste through agriculture and animal husbandry is caused by the lack of public knowledge about waste treatment.